Among 100 top company Performance of Real Estate Industry: Does Chief Financial Officer Matters? / Syaza Laili Sharipuddin ... [et al.] - Sharipuddin, Syaza Laili; Mohd Ayub, Nur Aeisya Firrzana; Mahassan, Nur Aqilla; Abdul Rahim, Memiyanty (2021)
Malaysia has a wide range of companies that are involved in the real estate sector. Real estate, land, buildings, air rights over the land as well as the ground beneath are examples of features covered in this industry. Real estate includes "land and the improvements connected with it," such as structures (buildings), crops, and even mineral rights (Shaukat 2010; Amadeo 2021). They have many similar features and are "real assets" in the sense that we can touch and feel them, they are grouped. This paper will examine the relationship between the characteristics of the CFOs and the financial performance of the companies in the real estate industry.Thus, the relationship between the CFO's characteristics and the financial performance will be measured based on eight (8) companies in the real estate industry that were listed in the Top 100 companies in Malaysia. The company involved in this study were Sunway Real Estate, SP Setia Berhad, Eco World Berhad, Tropicana Corporation Berhad, Mah Sing Group Berhad, UOA Development, TA Enterprise, and Eastern & Oriental Berhad. Apart from that, this study assessed the financial performance using two methods: return on asset (ROA) and return on equity (ROE). Rosikah, Prananingrum, Muthalib, Azis, and Rohansyah (2018) mentioned that ROA is used to assess a firm's potential to generate profits by utilizing the total owned assets in the future. The second method of calculating return on equity is to divide the total amount of money invested. Return on equity (ROE) can be regarded as a financial performance indicator determined by dividing net income by shareholders' equity.